Mental Toughness West Java Pencak Silat Athletes - Dedi Supriadi (STKIP Muhammadiyah Kuningan, 2023)
Mental toughness controls a person's emotional aspects, which becomes essential for athletes, especially martial athletes, especially pencak silat. This research aims to know the situation of the mental toughness of martial arts athletes. The research subjects used all pencak silat athletes who were members of PPLP West Java, as many as 17 people, consisting of 9 men and eight women. The research method uses a quantitative descriptive survey approach. The research instrument uses a questionnaire about mental toughness and data analysis using a quantitative analysis approach through statistics in the form of percentages. Of 17 research subjects, three people, or 17.7% of situation mental toughness, are in a low category. Ten people, or 58.8%, have mental toughness in the medium category and four with mental toughness in the wide variety. Female athletes own the low class; the medium type is owned by at least five men and five women, while four male athletes hold the high course. It is hoped that coaches must be able to understand the importance of the mental aspect in athletes because it will significantly affect their performance when competing